LITERATURE REVIEW: Pengaruh Etika Guru Biologi Dalam Meningkatkan Karakter Peserta Didik - Khairatunnisa, Khairatunnisa; Darussyamsu, Rahmawati; Ardi, Ardi (Al-Alam: Islamic Science Education Journal, 2024)
21st century learning requires students to think critically, find solutions to problems, and also aims to improve students' science literacy skills. The learning model applied by teachers is less varied due to several factors that make teachers less innovative in choosing learning models. The choice of learning model affects the implementation of the learning process in students. This research is an experimental research that aims to analyze the Inquiry Learning Model and its Relationship with the Science Literacy of Learners in High School in Biology Subjects. The inquiry learning model is one of the learning models that involves students' critical thinking skills in asking questions, seeking information, conducting systematic and procedural investigations so that students can formulate their own findings with confidence. This inquiry learning model will be collaborated with science literacy, which is whether it has an influence in improving students' science literacy skills. The research method used is a literature study of related articles. The results showed that there was an increase in science literacy